Natural polysaccharides exert anti-tumor effects as dendritic cell immune enhancers - Xiong, Hongtai; Han, Xinpu; Cai, Liu; Zheng, Honggang (Frontiers in Oncology, 2023)
With the development of immunotherapy, the process of tumor treatment is also moving forward. Polysaccharides are biological response modifiers widely found in plants, animals, fungi, and algae and are mainly composed of monosaccharides covalently linked by glycosidic bonds. For a long time, polysaccharides have been widely used clinically to enhance the body's immunity. However, their mechanisms of action in tumor immunotherapy have not been thoroughly explored. Dendritic cells (DCs) are a heterogeneous population of antigen presenting cells (APCs) that play a crucial role in the regulation and maintenance of the immune response. There is growing evidence that polysaccharides can enhance the essential functions of DCs to intervene the immune response. This paper describes the research progress on the anti-tumor immune effects of natural polysaccharides on DCs. These studies show that polysaccharides can act on pattern recognition receptors (PRRs) on the surface of DCs and activate phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT), mitogen-activated protein kinase (MAPK), nuclear factor-κB (NF-κB), Dectin-1/Syk, and other signalling pathways, thereby promoting the main functions of DCs such as maturation, metabolism, antigen uptake and presentation, and activation of T cells, and then play an anti-tumor role. In addition, the application of polysaccharides as adjuvants for DC vaccines, in combination with adoptive immunotherapy and immune checkpoint inhibitors (ICIs), as well as their co-assembly with nanoparticles (NPs) into nano drug delivery systems is also introduced. These results reveal the biological effects of polysaccharides, provide a new perspective for the anti-tumor immunopharmacological research of natural polysaccharides, and provide helpful information for guiding polysaccharides as complementary medicines in cancer immunotherapy.